OVARIAN STIMULATION WITH FOLLITROPIN-δ REDUCES RISK OF OVARIAN HYPERSTIMULATION SYNDROME: Follitropin-δ reduces Ovarian Hyperstimulation Syndrome risk - Perovic, Milan; Zecevic, Nebojsa; Bojovic Jovic, Dragana; Nozic Zecevic, Tatjana; Stojsavljević, Aleksandar; Nikolic, Gorana; Nikolic, Ana (Medical Research, 2024)
INTRODUCTION Ovarian stimulation (OS) during assisted reproductive technology (ART) carries the risk of ovarian hyperstimulation syndrome (OHSS). The risk is increased in polycystic ovary syndrome (PCOS). Recombinant DNA technologies have brought new generations of gonadotropins, such as Follitropin-δ. Individualized Follitropin-δ dosing, based on patient’s body weight (BW) and AntiMuellrian hormone (AMH), reduces OHSS risk. AIM To compare prevalence of OHSS and efficacy of OS with individualized Follitropin-δ and standard dosing with old generation gonadotropins in women with PCOS. MATERIAL AND METHODS Case-control study encompassed 24 women stimulated with individualized Follitropin-δ dosing (Study Group) and 48 women with standard old generation gonadotropin dosing (Control Group). Inclusion criteria: PCOS. Exclusion criteria: other causes of infertility. Study participants were matched according to age, BW, AMH and smoking status. RESULTS Prevalence of moderate (0% vs. 5.9%) and severe (0% vs. 17.6%) OHSS were significantly lower in Study Group (p=0.009). Duration of OS (9.06±1.53 vs. 10.00±1.13 days, p=0.01) and total gonadotropin dose (1,117.95±234.90 vs. 1,940.33±501.20 IU, p<0.001) were significantly lower in Study group. Number of good quality embryos was significantly higher in Study group (3.33±1.13 vs. 2.20±0.96 embyos, p<0.001). CONCLUSION The prevalence of moderate and severe OHSS is lower in OS with individualized Follitropin-δ dosing compared to standard dosing with older generations of gonadotropins. The effectiveness of OS in the study groups did not differ significantly, except the shorter duration of OS, a lower applied total gonadotropin dose and a significantly higher number of good quality embryos, which were recorded in Study group.